PTU-093 An Evaluation Of An Ibd Advice Service: Is It Meeting Its Service Aims?. (9th June 2014) - Collins, G; Sastrillo, M; Duncan, J
Abstract : Introduction: The provision of a dedicated and accessible IBD advice service (AS) is a key element of IBD management and, often, the responsibility of the Advanced, or specialist, IBD Nurse according to the N-ECCO Consensus statements. UK IBD Standards require IBD patients to have rapid access to specialist advice before the end of the next working day (EONWD). Our AS aims to provide timely access to clinical advice, support and acts as a point of contact to co-ordinate the patient journey. We evaluated if our advice service was meeting these goals. Methods: Over a 5 week period (23 working days) during October and November 2013, all contacts to the AS of a central London tertiary IBD service were recorded. Patients either called and left a message on an answering machine, or emailed a dedicated email address. Two experienced IBD CNS' collected data during each encounter. This included demographics of gender, age, and diagnosis; the format of contact (phone/email); if a medical opinion (IBD specialist or IBD registrar/fellow) was sought; time to response, and amount of time spent on each contact. The content of the encounter (administrative, clarification, a new query, or a symptomatic change/flare) was documented along with the response (administrative, information, results, treatment changes, medical decision), and the follow up required for the patient (routine, earlier or urgent outpatient appointment, or hospital admission/presentation to AandE). Results: 262 contacts were made to the AS. 4 could not be re-contacted and 23 had missing data, leaving 235 complete encounters for analysis, of which 3 enquiries were non-IBD related. Those who contacted the AS were predominantly female (148/235, 62.98%), between 26–35 (97/235, 41.28%), with a diagnosis of Crohn's Disease (160/235, 68.09%), the latter reflecting the tertiary nature of our IBD service. 99.15% (233/235) of contacts were replied to by EONWD, with 38.29% (90/235) answered within 12 h. The majority of contacts (85.11%) were for clinical reasons with 14.89% administrative (35/235). 51/235 (21.70%) pertained to flares. 88.94% (209/235) were autonomously handled by the IBD CNS though IBD Consultant/Fellow support was required in 26 cases. AandE presentation was recommended to 2 patients (2/235, 0.85%) and 25(10.64%) had their outpatient appointment brought forward, meaning the vast majority were clinically managed without the need for additional outpatient review. Conclusion: Our IBD advice service provides patients with rapid access to specialist advice, symptom management and disease-specific information, meeting UK national standards. The IBD CNS' expertise means clinical enquiries can be effectively managed whilst avoiding additional, unnecessary burden to the patient and to outpatient clinics. Disclosure of Interest: None Declared.